Swapping settings: Researching information literacy in workplace and in educational contexts - Hampson Lundh, Anna; Limberg, L.; Lloyd, A. (University of Sheffield, 2013)
© the authors, 2013.Introduction. Information literacy research is characterised by a multitude of interests, research approaches and theoretical starting-points. Challenges lie in the relevance of research to professional fields where information literacy is a concern, and the need to build a strong theoretical base for the research area. We aim to lay a foundation for a discussion on how researchers may approach issues of norms and values in information literacy, through a comparison between selected studies in educational and workplace settings respectively. Method. Eight recent empirical studies on information literacy were selected for analysis; four of educational settings and four of workplace settings. Analysis. A comparison between the eight studies was made with a focus on conceptualisations of information literacy and approaches to issues of norms and values. Results. Two approaches to norms and values in relation to information literacy were identified in the eight studies. The studies conducted with students have a clear evaluative approach, while three of the workplace studies are characterised by an explorative approach. One workplace study has an intermediate position. The evaluative and explorative approaches are then swapped, to examine how relevant each approach is in the context of the other setting. In this way, we are able to discuss underlying perspectives that direct research. Conclusion. Our analysis suggests that well-chosen theoretical perspectives are necessary if information literacy researchers wish to influence professional practice.